Literary Obscenities U.S. Case Law and Naturalism after Modernism - Bachman, Erik (Penn State University Press, 2017)
In Literary Obscenities, Erik Bachman offers a comparative historical account of the parallel development of legal obscenity and literary modernism in this period. Getting Off the Page demonstrates that obscenity trials in the early twentieth century staged a wide-ranging cultural debate about the broader ramifications of the printed word's power to "deprave," "excite," and offend-or, more generally, to incite emotion and shape behavior. Bachman shows that far from seeking simply to transgress cultural norms or sexual boundaries, proscribed authors such as Wyndham Lewis, Erskine Caldwell, Lillian Smith, and James T. Farrell refigured the capacity of writing to evoke the obscene so that readers might become aware of the social processes by which they were being turned into mass consumers, voyeurs, and racialized subjects.